Tear meniscus evaluation after microkeratome laser in situ keratomileusis, femtosecond laser and femtosmile laser techniques using anterior segment optical coherence tomography - Shaaban YM (Dove Medical Press, 2018)
Yasmine Maher Shaaban, Tamer Abdel Fattah Badran Faculty of Medicine, Ain Shams University, Cairo, Egypt Purpose: The purpose of this study was to compare the effects of three different corneal refractive surgeries: microkeratome laser in situ keratomileusis (LASIK), femtosecond laser in situ keratomileusis (FS-LASIK) and femtosecond small incision lenticule extraction (FS-SMILE) on 6-month postoperative stability of tear film to provide a basis for selection of operative procedures. Patients and methods: This is a prospective, randomized, comparative study that included 90 eyes of three equal groups of patients. Each group was subjected to a different laser technique: LASIK, FS-LASIK and FS-SMILE. Using anterior segment spectral domain optical coherence tomography (AS-SD-OCT), the lower tear meniscus parameters were measured preoperatively and 1 week, 1 month, 3 months and 6 months postoperatively. Changes were studied and compared. Results: There was a statistically significant difference in tear meniscus height (TMH) between FS-SMILE and FS-LASIK in the first week (P = 0.003) and first month (P = 0.002) with no statistically significant difference between both techniques at 3 and 6 months postoperatively. In FS-SMILE, TMH returned to 95% of its preoperative level after 1 month. There was no statistically significant difference in TMH between FS-LASIK and microkeratome LASIK techniques after 1 week and 1 month, but there was a statistically significant difference between both techniques in 3 months (P = 0.019) and 6 months (P = 0.032). Tear meniscus area (TMA) showed no statistically significant difference between FS-SMILE and FS-LASIK at all points of follow-up, but there was a statistically significant difference between both techniques and microkeratome LASIK (all P < 0.05). Microkeratome LASIK parameters failed to reach the preoperative level till 6 months. Conclusion: Early recovery of the lower TMH can be achieved as early as 1 month postoperatively with the FS-SMILE technique compared to FS-LASIK and microkeratome LASIK techniques. Keywords: LASIK, tear meniscus, optical coherence tomography